2010
DOI: 10.2463/mrms.9.217
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of ADC for Non-mass-like Breast Lesions on MR Imaging

Abstract: We assessed the usefulness and limitations of utilizing apparent diŠusion coe‹cient (ADC) values on diŠusion-weighted imaging (DWI) for the diŠerential diagnosis of benign and malignant non-mass-like breast lesions. We retrospectively reviewed 27 such lesions (16 malignant, 11 benign) detected on magnetic resonance (MR) imaging and analyzed the enhancing patterns of dynamic contrast-enhanced DCE-MRI (distribution and internal enhancement), kinetic curve patterns, and ADC values. All images were obtained with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 31 publications
4
55
2
Order By: Relevance
“…These lesions are commonly associated to NME pattern and frequently display less suspicious kinetic enhancement characteristics 17,18 , which is in agreement to our own results. When microinvasion or frank invasion ensues, the imaging findings tend to become more typically suspicious 19 .…”
Section: Discussionsupporting
confidence: 93%
“…These lesions are commonly associated to NME pattern and frequently display less suspicious kinetic enhancement characteristics 17,18 , which is in agreement to our own results. When microinvasion or frank invasion ensues, the imaging findings tend to become more typically suspicious 19 .…”
Section: Discussionsupporting
confidence: 93%
“…Ring enhancement was found in one malignant case. Homogenous enhancement was found in 15 lesions, 2 (13.3%) were benign and 13(86.7%) were malignant.In our study there was no statistical correlation between the pathologically proven benign and malignant lesions regarding their enhancement pattern except the non enhancing internal septations and this may be attributed to the small number of the studied patients, however our all pathologically proven benign cases did not show enhancing internal septations (100 % specificity).Imamura et al [27] found in his study that malignant non mass lesions tended to show either segmental or branching ductal distribution, and when lesions with these patterns are considered malignant the sensitivity & specificity were 68.8% and 63.6% respectively. He also reported that using the enhancement pattern in differentiation between benign and malignant lesions is often difficult with non mass like enhancement as there is no standarized method for interpreting them.…”
contrasting
confidence: 52%
“…Imamura et al [27] found in his study that malignant non mass lesions tended to show either segmental or branching ductal distribution, and when lesions with these patterns are considered malignant the sensitivity & specificity were 68.8% and 63.6% respectively. He also reported that using the enhancement pattern in differentiation between benign and malignant lesions is often difficult with non mass like enhancement as there is no standarized method for interpreting them.…”
Section: Citationmentioning
confidence: 95%
“…The below-threshold ADCs of most high-risk lesions are not surprising owing to their histologic similarity to malignant lesions. By far, the majority of nonmalignant lesions reported in prior DW imaging studies were fibroadenomas and fibrocystic changes (12,19,22,36,42,43). Fibroadenomas are generally presumed to have higher ADCs because of stromal myxoid change and consequent higher water mobility (24).…”
Section: Intra-and Interobserver Variabilitymentioning
confidence: 99%